Fashion, Identity, and Power in Modern Asia (East Asian Popular Culture, 2018)
This edited volume on radical dress reforms in East Asia takes a fresh look at the symbols and languages of modernity in dress and body. Dress reform movements around the turn of the twentieth century in the region have received little critical attention as a multicultural discourse of labor, body, gender identity, colonialism, and government authority. With contributions by leading experts of costume/textile history of China, Korea, and Japan, this book presents up-to-date scholarship using diverse methodologies in costume history, history of consumption, and international trade. Thematically organized into sections exploring the garments and uniforms, accessories, fabrics, and fashion styles of Asia, this edited volume offers case studies for students and scholars in an ever-expanding field of material culture including, but not limited to, economic history, visual culture, art history, history of journalism, and popular culture. Fashion, Identity, and Power in Modern Asia stimulates further research on the impact of modernity and imperialism in neglected areas such as military uniform, school uniform, women's accessories, hairstyles, and textile trade.